ACTIVATION METHOD OF CLEANING PROCESS GAS - Rakhimberlinova Zh.B.,; Takibayeva A.T.,; Nazarova O.G.,; Iskakov A.R.,; Musina G.N.,; Kulakov I.V., (Academic Scientific Journal of Chemistry, 2020)
This article presents the results of joint research of "ABsalut Ecology" LLP with Karstu of industrial electrochemical aeroion plants B30-500 and AP-21, capable of cleaning technological gas emissions from toxic impurities SO2 (at least 90%), NOx (at least 80%), CO2 (at least 90%) and dust particles (99.9%); with the return to production of part of the burned carbon (in the form of fine soot). It was found that in the discharge zone of the V30-500 and AP-21 installations, the active factors affecting the chemical process are: high voltage of the electric field ; secondary ionization of substances; polarization of molecules; high temperature; photoionization; microwave radiation; shock wave. Two processes take place simultaneously in the reaction zone of the plants: activation and reduction of CO2, CO, NOx, and SO2 oxides to elementary substances in the core of the electronic injector. Reduction of CO2, CO, NOx, and SO2 oxides in the reaction zone proceeds simultaneously by various mechanisms: catalytic reduction and dissociation. It is established that the catalytic system in the installation is an electronic injector, which serves as a source of active particles that determine the rate of chemical reactions. Reducing agents CO, NH3 are present in the gas to be treated , and are also formed in the reaction zone of the plant. As a result of the reactions, elementary substances are formed. The speed constants of elementary processes in a discharge strongly depend on the electric field strength, and the speed of individual processes may depend in a nonlinear way on the current density, so by changing these parameters, you can change the selectivity and speed of recovery processes in the installation. It is shown that ionization and dissociative processes with the formation of various radicals and ions are feasible in non-equilibrium weakly ionized plasma. The degree of capture of aerosols and dust increases with a decrease in the size of dust-like particles, and in dry electric filters, on the contrary, falls to zero. The ways of increasing the efficiency of technological gas treatment plants (geometric parameters of new plants, increasing their productivity, using new high-voltage power sources, flotation and filtration devices, and dispatching control systems) were determined. The efficiency of the gas treatment plant does not decrease when the particle size of the captured aerosols decreases, starting from the size of about 5 microns and lower, the cleaning efficiency approaches 100%. The research results are shown as graphs that show the concentration of gas before and after treatment. The degree of air purification from dust particles and aerosol impurities ranges from 60% to 99%.